Does Bank Diversification Affect Funding Cost? Evidence from The U.S. Banks - Dung Viet Tran (Asian Academy of Management Journal of Accounting and Finance, 2020)
We investigate how diversification affects the U.S. bank holding companies’ funding cost. We document consistent evidence of a lower deposit rates for banks that engage more in non-traditional banking activities. The quantile regressions which dissect the behaviour of banks at the right tail of deposits costs distribution, point out the leveraged effect of diversification is more pronounced with lower-deposits costs banks. The study also suggests diversified banks enjoy lower funding cost during the crisis. Our study is of interest to regulators and policymakers.